For an Interdisciplinary Approach to the Modern Social Contract: Tax Policies, Racial Inequalities and Human Rights - Nascimento, Flávio Batista; Tolentino, Philipe Anatole Gonçalves (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
This article intends to identify how race and fiscal policies affect the aspect of the materialization of human rights and racial inequalities in the modern social contract. For this, it will use the interdisciplinarity of the field of study of the new fiscal sociology, which suggests that fiscal policies provide the state apparatus with resources, define how these will be spent and distribute their burden to the whole of society. It is through the tax that the commitment between taxpayers and the tax authorities is expressed and maintained, in the last instance, between individuals and the State. Without tax there is no property and much less representation. However, this approach alone is not enough, so we make use of the category of race and its political, economic dimension in power relations and the production of subjectivity, which points to the emergence of racism as a procedural and historical phenomenon. It is not a product of the behavior of individuals, in fact, its dynamics produce individuals, and their subjectivities are crossed by racial conditions. In such a way that the tax system cannot be neutral as to the political dimensions of racial inequalities. As a modern event, human rights will not remain unscathed in the face of changes that have taken place within budget definitions and racial inequalities, on the contrary, their emergence is only possible given the socioeconomic conditions of this process.